2020
DOI: 10.1016/j.chembiol.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Targeted Degradation Strategy for Oncogenic KRASG12C

Abstract: Highlights d A comprehensive degrader molecule (PROTAC) library for KRAS G12C is described d Lead compound degrades GFP-KRAS G12C in a CRBNdependent manner d Challenges and solutions for achieving endogenous KRAS G12C degradation are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
210
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 75 publications
2
210
0
1
Order By: Relevance
“…Since PROTACs often exhibit poor cell‐penetration due to their high molecular weight and presence of many hydrogen bond acceptors and donors, we sought to evaluate cellular permeability and intracellular CRBN engagement using a previously described cellular assay . Briefly, this is a competition‐based assay that measures the ability of a degrader molecule to displace BRD4 BD2 ‐directed CRBN ligands, which subsequently leads to the restoration of BRD4 BD2 ‐GFP signal.…”
Section: Resultsmentioning
confidence: 99%
“…Since PROTACs often exhibit poor cell‐penetration due to their high molecular weight and presence of many hydrogen bond acceptors and donors, we sought to evaluate cellular permeability and intracellular CRBN engagement using a previously described cellular assay . Briefly, this is a competition‐based assay that measures the ability of a degrader molecule to displace BRD4 BD2 ‐directed CRBN ligands, which subsequently leads to the restoration of BRD4 BD2 ‐GFP signal.…”
Section: Resultsmentioning
confidence: 99%
“…Using an overexpressed and tagged construct of the target proteins allows easy monitoring (e.g. GFP tagged proteins), quick setup and time resolved degradation in a high throughput format but due to potential high expression levels weak degraders might be missed or false positive PROTACs identified which only initiate degradation of the tag instead of the target protein itself . CRISPR/Cas modifications of the endogenous target protein adding a small tag (HA‐tag or NanoLuc®) are more time consuming but can increase sensitivity due to endogenous protein levels and a more favorable target protein/E3 ligase ratio.…”
Section: Degradation Of Untagged Target Proteinsmentioning
confidence: 99%
“…A key challenge in PROTAC design to date is the selection of the optimal linker to connect these two binding components. In most cases, linkers of various lengths are screened using synthetically accessible chemistry [15][16][17][18][19] . In some cases, it was shown that a protein-protein interface between the target and the E3 ligase, including interactions with the linker, is important for cooperativity 4 .…”
Section: Introductionmentioning
confidence: 99%